Klaus Mann's Mephisto: A Secret Rivalry - Peter T. Hoffer (Studies in 20th & 21st Century Literature, 1989)
Critics of the 1960s and 1970s have focused their attention on Klaus Mann's use of his former brother-in-law, Gustaf Gründgens, as the model for the hero of his controversial novel, Mephisto, while more recent critics have emphasized its significance as a work of anti-Fascist literature. This essay seeks to resolve some of the apparent contradictions in Klaus Mann's motivation for writing Mephisto by viewing the novel primarily in the context of his life and career. Although Mephisto is the only political satire that Klaus Mann wrote, it is consistent with his life-long tendency to use autobiographical material as the basis for much of his plot and characterization. Mann transformed his ambivalent feelings about Gründgens, which long antedated the writing of Mephisto, into a unique work of fiction which simultaneously expresses his indignation over the moral bankruptcy of the Third Reich and reveals his envy of Gründgens's career successes.
Keywords: 1960s; 1970s; Klaus Mann; Gustaf Gründgens; Mephisto; anti-Fascist literature; anti-Fascist; literature; life; political satire; autobiographical; plot; characterization; Third Reich; career